Penerapan Evidence Based Nursing: Terapi Brandt-Daroff pada Pasien Vertigo dengan Nyeri Akut di ICU 3 RSUD Gunung Jati Kota Cirebon - Rizky Prihastin Utami; Dewi Erna Marisa; Ahmad Syarifudin; Idit Pitriati (Jurnal Ilmu Kesehatan dan Gizi, 2026)
Vertigo is a disorder of the vestibular system characterized by spinning sensations, balance disturbances, nausea, vomiting, and activity limitations caused by changes in body position. In critically ill patients treated in the Intensive Care Unit (ICU), vertigo may lead to various nursing problems such as risk of falls, impaired physical mobility, anxiety, and acute pain caused by abnormal vestibular stimulation that triggers tension in the head and neck muscles. Vertigo management is generally carried out using pharmacological therapy; however, long-term medication use may cause side effects, therefore evidence-based non-pharmacological interventions are needed. One intervention that can be applied is Brandt-Daroff therapy as a vestibular rehabilitation exercise to help the body adapt to balance disturbances. The purpose of this scientific paper was to determine the application of Evidence-Based Nursing through Brandt Daroff therapy in vertigo patients with acute pain nursing problems in ICU 3 of Gunung Jati Regional Hospital, Cirebon City. The method used was a case study approach through emergency and critical nursing care processes. Assessment was conducted using primary and secondary survey approaches, followed by gradual Brandt-Daroff therapy according to the patient’s condition. Evaluation was carried out by assessing changes in pain intensity, comfort level, body balance, and patient mobilization ability. The results showed that Brandt-Daroff therapy was able to reduce acute pain intensity, decrease vertigo sensations, improve patient comfort, and gradually increase balance and activity tolerance. The conclusion of this scientific paper indicates that Brandt-Daroff therapy is effective as an evidence-based non-pharmacological nursing intervention in helping overcome acute pain in vertigo patients in the ICU.